THE INFLUENCE OF OBESITY AND BLOOD PRESSURE ON INDEXES OF CARDIAC FUNCTION: ECHOCARDIOGRAPHIC ASSESSMENT - AKAHOSHI, Ryuichiro; NISHIGAMI, Kazuhiro; YOSHIMURA, Rikiya (Japanese Journal of National Medical Services, 1998)
Cardiac function and structure of 193 hypertensive and obese subjects in total were evaluated by two-dimentionally guided M-mode echocardiographic findings. Following results were obtained. 1) A weak correlation was observed between body mass index and either left ventricular dimension in diastole or left atrial dimension in the normotensive subjects. 2) After adjustments of age and sex, hypertensive subjects had greater left atrial dimension, left ventricular mass, interventricular septal thickness and left ventricular posterior wall thickness than normotensive subjects, whereas left ventricular dimension in diastole was similar between both groups. On the other hand, obese subjects had greater left ventricular dimension in diastole, left atrial dimension and left ventricular mass than nonobese subjects, whereas left ventricular wall thickness was similar between both groups. 3) Increased left ventricular mass in the hypertensive and obese subjects resulted respectively from left ventricular wall thickening and chamber dilatation.